An Empirical Analysis of Liquidity Risk in Chinese Commercial Banks - YUAN, QI (2018)
Liquidity risk generated in commercial banks due to the nature of bank functions. It can influence a bank’s solvency and bring the bank to a vulnerable position to unexpected cash outflow. If liquidity risk in commercial banks cannot be managed well, it may cause bankruptcy or even big scale financial crisis through the chain effect such as the bankruptcy of Lehman Brothers and the global financial crisis. This research aims to do an empirical analysis of liquidity risk in Chinese commercial banks. The sample includes 40 selected Chinese commercial banks from 2013 to 2017. The quantitative research methods are adopted for this study. According to the empirical results, the first finding is that though there is still surplus liquidity exist in Chinese commercial banks, the liquidity risk in Chinese commercial has increased rapidly during the research period, especially in small banks. Secondly, the determinants of liquidity risk in Chinese commercial banks include both bank-specific factors and macro factors such as ROAE, CAP, LLRR, SPEC, IRL, IRB and GDP lag (-1). Thirdly, the determinants for big banks are different from that for small banks. Generally, the liquidity risk in big banks is more sensitive to macro factors such as GDP lag (-1) and inflation rate than small banks. The largest impact on liquidity risk in big banks is loan loss reserve ratio while that of small banks is the interest rate on loans.